TRAINING COURSE AT PARFOR: REFLECTIONS AND/OR IMPACTS ON THE PROFESSIONAL AND PERSONAL LIFE OF ALTO JURUÁ ACADEMICS - Aldenora dos Santos Lima, Maria; Fernandes Sessa Mendonça, Gizeli; Aparecido Gonçalves, Israel (Revista Gênero e Interdisciplinaridade, 2023)
This article presents the personal and formative trajectory, through the memorial genre, of final works to conclude the pedagogy course, of the Basic Education Teacher Training Program (PARFOR), carried out by the Federal University of Acre-UFAC, in the Municipality of Porto Walter (Acre).The memorial emphasized the experiences acquired throughout the academic career in the Amazon context. Furthermore, the methodology was based on the works of Souza (2008); Prado and Soligo (2007), and structured interviews were carried out, as well as the production and discussion of texts in the subjects Research in Education, TCCI and TCCII. In total, 38 teachers participated in the research, which showed that teacher training at ACRE, through the PARFOR program, is extremely relevant for teachers who learned about new didactic and theoretical instruments, improving the quality of their classes in the Region Amazon.